Electrical Stimulation Elicits Neural Stem Cells Activation: New Perspectives in CNS Repair - Huang, Yanhua; Li, YeE; Chen, Jian; Zhou, Hongxing; Tan, Sheng (Frontiers in Human Neuroscience, 2015)
Researchers are enthusiastically concerned about neural stem cell (NSC) therapy in a wide array of diseases, including stroke, neurodegenerative disease, spinal cord injury, and depression. Although enormous evidences have demonstrated that neurobehavioral improvement may benefit from NSC-supporting regeneration in animal models, approaches to endogenous and transplanted NSCs are blocked by hurdles of migration, proliferation, maturation, and integration of NSCs. Electrical stimulation (ES) may be a selective non-drug approach for mobilizing NSCs in the central nervous system. This technique is suitable for clinical application, because it is well established and its potential complications are manageable. Here, we provide a comprehensive review of the emerging positive role of different electrical cues in regulating NSC biology in vitro and in vivo, as well as biomaterial-based and chemical stimulation of NSCs. In the future, ES combined with stem cell therapy or other cues probably becomes an approach for promoting brain repair.